Simultaneous Estimation and Validation of Esomeprazole and Domperidone by HPTLC in Pure and Pharmaceutical Dosage Forms - ROOSEWELT, C.; MAGESH, AR.; SHEEJA REKHA, A.G.; SHANMUGA PANDIAN, P.; GUNASEKARAN, V. (Asian Journal of Chemistry, 2010)
A simple, rapid, sensitive high performance thin layer chromatographic method has been developed and validated for the simultaneous estimation of esomeprazole and domperidone in pure and pharmaceutical dosage form. It was performed on TLC plate pre-coated with silica gel 60F254 as a stationary phase using mobile phase composing of chloroform:acetonitrile:ammonia (5:10:0.25) and the detection was carried out in absorbance/reflectance mode at 222 nm showing Rf value 0.76 for esomeprazole and 0.89 for domperidone. The percentage estimation of labeled claims of esomeprazole and domperidone from marketed tablet were found to be 99.55 and 99.60, respectively. The method was validated in terms of accuracy, precision, specificity and ruggedness. Linearity was observed between 600-1400 μg/mL for domperidone and 1200-2800 μg/mL for esomeprazole. The percent recovery study was done by standard addition method and were found in the range of 99.73 and 99.59, respectively. The proposed method is precise, accurate and can be used for routine analysis of esomeprazole and domperidone in tablets.